The Fisher queen's dynasty - Kavita Kane (Westland publications, 2017)
I learnt to love like a man-to love without feelings. And I shall never forget this lesson.' Matsyagandha, Daseyi, Yojanagandha - the queen of Hastinapur, Satyavati. Abandoned as a baby, preyed on by a rishi, she hardens herself, determined that the next time she is with a man, she will be the one to win. And win she does: the throne of Hastinapur for herself, and the promise that her sons will be heirs to the kingdom. But at what cost? In a palace where she is disdained and scorned, Satyavati must set aside her own loss and pain if she is to play the game of politics. She learns to be ruthless, unscrupulous - traits that estrange her from everyone around. Everyone, except the man she cheated of his birthright. A piercing, insightful look at the grand matriarch of the Kuru family, the woman who set off the sequence of events that ended in the bloody battle of Kurukshetra, The Fisher Queen's Dynasty will re-align your reading of the Mahabharata.